Redefining supply management׳s contribution in services sourcing. Issue 1 (March 2015) - Ellram, Lisa; Tate, Wendy L.
Abstract The services economy is growing in magnitude and impact. As purchased services contribute as both a source of cost and as a source of performance improvement, services spend is gaining the attention of practitioners and academics interested in improving the purchase and management of services. In-depth case study research shows that purchasing services differ from purchasing goods in several important ways. When a company procures services, SM׳s involvement does not necessarily grow over time. SM׳s involvement is not a "given" so SM must often be "invited" based on the perception that it will contribute favorably to the outcome. Because meaningful involvement may require very different types of involvement, varying from primary control to a consultative role, this research offers a modified definition of SM meaningful involvement. Finally, a managerial framework is developed to help guide decision-making for more efficient and effective purchase of services.